A Forensic Pragmatic Analysis of Impoliteness Strategies in Financial Blackmail - Zahraa Aamir Kamil; Muayyad Omran Chiad (مجلة الباحث, 2025)
This study investigates impoliteness strategies in cyber blackmail messages sent by offenders within Iraqi digital contexts. Based on Culpeper’s (1996) model of impoliteness, the analysis focuses on real-life cases involving male and female perpetrators. The data reveal recurring patterns of threats, verbal aggression, and face-threatening acts (FTAs), particularly in financial blackmail. This study hypothesizes that bald on record is the most frequently used strategy of impoliteness by blackmailers, while the sarcasm strategy is the least utilized. The forensic linguistic approach adopted here aims to uncover how impoliteness is linguistically constructed to manipulate, intimidate, or control victims. Finally, the study finds that negative impoliteness is the most frequently utilized strategy by both males and females in financial blackmail, whereas sarcasm has been the least